Perubahan Sosial Ekonomi Masyarakat Pasca Pembangunan Jalan Tol Ungaran-bawen (Faculty of Social Science, Universitas Negeri Semarang, 2015)
Construction of toll road is part of the national development program to improve the economic growth of society. The construction of Toll Road Ungaran-Bawen managed by PT Trans Marga Central Java cause some land of Kandangan Village affected by lane of tol road must be relocated. The purpose of this study to 1) knowing profile of the socio-economic life of Dusun Geneng society before and after the construction of toll roads. 2) Knowing the socio-economic changes of Dusun Geneng society after the construction of Ungaran-Bawen toll road. The results showed before the construction of Ungaran-Bawen toll road Desa Kandangan society is a simple rural communities and classified of households as poor. After the relocated families receive the compensation, they can improve their live better. In the other hands, the socio-economic condition of society who not relocated is unchanged. After the construction of Ungaran-Bawen toll road, society Kandangan have progress that occurs on aspects of social and economic life such as socio-economic status, level of education, lifestyle, patterns of public relations, the level of income and livelihood.